An assessment of the centrally acting muscle relaxant tolperisone on driving ability and cognitive effects compared to placebo and cyclobenzaprine. (10th May 2020) - Caron, Judy; Kaye, Randall; Wessel, Thomas; Halseth, Amy; Kay, Gary
Abstract: What is known and objective: Tolperisone is a centrally acting muscle relaxant under development in the United States as a treatment for acute and painful symptoms of muscle spasms. The objective of this three‐way, randomized, blinded, three‐period crossover study was to assess the safety and cognitive effects of tolperisone compared to placebo and the widely used muscle relaxant cyclobenzaprine in healthy volunteers. Methods: Subjects were randomized to 1 of 3 treatment arms to receive tolperisone (150 mg), cyclobenzaprine (10 mg) or placebo 3 times per day (TID) in 3 separate study periods. Subjects completed a driving test on the Cognitive Research Corporation's Driving Simulator (CRCDS Mini‐Sim), a validated driving simulator, on day 1 at time to maximum plasma concentration, on day 2 before the morning dose of study drug and on day 3 at steady state following the morning dose. Subjects were assessed on various driving parameters and on a computer‐administered digit‐symbol substitution test (CogScreen symbol digit coding test). The driving scenario is a monotonous 100 km highway route on which subjects are instructed to maintain speed and lane position. Results and discussion: The performance of subjects who had received tolperisone was not significantly different from those who had received placebo in terms of the primary end point: standard deviation of lateral position, a measure of weaving. Subjects who had received tolperisone also performed comparably to those who had received placebo on a range of secondary measures assessing driving ability, cognition and psychomotor performance. In contrast, subjects who had received cyclobenzaprine showed significant impairment compared to placebo ( P < .01) on the primary end point of standard deviation of lateral position and on the majority of the secondary end points of driving ability. Despite their markedly poorer driving performance after receiving cyclobenzaprine, few subjects reported feeling unsafe to drive on day 1 (10.3%) and day 2 (3.4%). The incidence of adverse events was similar for tolperisone (36.4%) and placebo (29.0%) and was greater for cyclobenzaprine (45.4%). What is new and conclusion: Subjects who received tolperisone (150 mg TID) experienced no impact on various measures of driving, self‐reported sleepiness and cognition measures compared to placebo, in contrast to those who received the widely used muscle relaxant cyclobenzaprine (10 mg TID). Abstract : Tolperisone is a centrally acting muscle relaxant under development for the treatment of acute and painful symptoms of muscle spasm. In this study of driving ability and cognitive effects, subjects who received tolperisone experienced no impact on measures of driving, self‐reported sleepiness, or cognition compared to placebo, in contrast to those who received the widely used muscle relaxant cyclobenzaprine.